Distinct Evolutionary Origins of Intron Retention Splicing Events in NHX1 Antiporter Transcripts Relate to Sequence Specific Distinctions in Oryza Species - Sellamuthu, Gothandapani; Jegadeeson, Vidya; Sajeevan, Radha Sivarajan; Rajakani, Raja; Parthasarathy, Pavithra; Raju, Kalaimani; Shabala, Lana; Chen, Zhong-Hua; Zhou, Meixue; Sowdhamini, Ramanathan; Shabala, Sergey; Venkataraman, Gayatri (Frontiers in Plant Science, 2020)
The genome of Asian cultivated rice (Oryza sativa L.) shows the presence of six organelle-specific and one plasma membrane (OsNHX1-7) NHX-type cation proton antiporters. Of these, vacuolar-localized OsNHX1 is extensively characterized. The genus Oryza consists of 27 species and 11 genome-types, with cultivated rice, diploid O. sativa, having an AA-type genome. Oryza NHX1 orthologous regions [gene organization, 5' upstream cis elements, amino acid residues/motifs] from closely related Oryza AA genomes cluster distinctly from NHX1 regions from more ancestral Oryza BB, FF and KKLL genomes. These sequence-specific distinctions also extend to two separate intron retention (IR) events involving Oryza NHX1 transcripts that occur at the 5' and 3' ends of the NHX1 transcripts. We demonstrate that the IR event involving the 5' UTR is present only in more recently evolved Oryza AA genomes while the IR event governing retention of the 13th intron of Oryza NHX1 (terminal intron) is more ancient in origin, also occurring in halophytic wild rice, Oryza coarctata (KKLL). We also report presence of a retro-copy of the OcNHX1 cDNA in the genome of O. coarctata (rOcNHX1). Preferential species and tissue specific up- or down-regulation of the correctly spliced NHX1 transcript/ 5' UTR/13th intron-retaining splice variants under salinity was observed. The implications of IR on NHX1 mRNA stability and ORF diversity in Oryza spp. is discussed.